Exclusion in the all-pay auction: An experimental investigation - Dietmar Fehr; Julia Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
Contest or auction designers who want to maximize the overall revenue are frequently concerned with a trade-off between contest homogeneity and inclusion of bidders with high valuations. In our experimental study, we find that it is not profitable to exclude the most able bidder in favor of greater homogeneity among the remaining bidders, even if the theoretical exclusion principle predicts otherwise. This is because the strongest bidders considerably overexert. A possible explanation is that these bidders are afraid they will regret a low but risky bid if they lose and thus prefer a strategy which gives them a lower but secure pay-off.
Keywords: C72; C92; D84; 330; experiments; contests; all-pay auction; heterogeneity; regret aversion